From Painting to Picturebook: Bhajju Shyam’s Insider Indigenous Art - Indraprastha University, India (IAFOR Journal of Arts & Humanities)
An outsider’s perspective has historically dominated representation of Indian Indigenous communities. Adivasi individuals have borne the brunt of primitivism encouraged by anthropologists, artists, writers, and administrators. An insider’s perspective is missing. Bhajju Shyam, a traditional Pardhan singer-storyteller, from the larger Gond tribe, negotiates with primitivism via “Gond painting” in the contemporary Anglophone picturebook. An insider, bearer of a ritual bardic cultural function, narrates the story of his work and his community using the medium at hand. This is a powerful reversal that potentially battles the harm visited upon Indigenous Indian communities for centuries. My research uses literary and visual analysis of the picturebooks, as well ethnographic interviews with the Adivasi artists, to explore artistic agency exercised in the illustration of picturebooks. In this essay, I focus my analysis on the 2014 Creation, a collection of origin stories found in the Pardhan Gond repertoire. I argue that a close reading of Creation reveals Bhajju Shyam’s strategic intent in composing a self-aware insider’s history of the artform, and by extension, reveals a history of a marginalized group that has been portrayed as a community of noble savages.